2022
DOI: 10.31289/jkbm.v8i2.6675
|View full text |Cite
|
Sign up to set email alerts
|

Peran Kepuasan Kerja dan Komitmen Organisasi Memediasi Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan

Abstract: The purpose of this study was to explain the role of job satisfaction and organizational commitment to mediate the efffect of organizational culture on employee performance. The population of this research is the employees of PT. Indomarco Prismatama (Indomaret) Pangkalpinang, totaling 115 people. The analytical tool used is path analysis using SEM method (struktural equation modeling) using SmartPLS 3. The results of the study indicate that organizational culture had a positive and significant effect on satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
1
8
0
4
Order By: Relevance
“…In Baluyos et al (2019), Heidarzadeh Hanzaee & Mirvaisi (2013 and Mira et al (2019) study, job satisfaction is reported to positively and significantly affect employee performance. In Panjaitan's (2022), Ali & Zia-ur-Rehman (2014) and Basher Rubel & Kee (2014) previous studies, job satisfaction is reported to positively mediating affected employee performance. Organizations need employees' level of job satisfaction that is capable of improving employee performance.…”
Section: Job Satisfaction As the Mediator On Employee Performancementioning
confidence: 85%
See 1 more Smart Citation
“…In Baluyos et al (2019), Heidarzadeh Hanzaee & Mirvaisi (2013 and Mira et al (2019) study, job satisfaction is reported to positively and significantly affect employee performance. In Panjaitan's (2022), Ali & Zia-ur-Rehman (2014) and Basher Rubel & Kee (2014) previous studies, job satisfaction is reported to positively mediating affected employee performance. Organizations need employees' level of job satisfaction that is capable of improving employee performance.…”
Section: Job Satisfaction As the Mediator On Employee Performancementioning
confidence: 85%
“…This can be observed through factors such as work morale, discipline, and achievement. Job satisfaction can be perceived both within the job-related context and outside of it, or as a combination of both (Panjaitan, 2022;Hünefeld et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Pemenuhan pekerjaan akan semakin mengembangkan pelaksanaan yang representatif Pemenuhan pekerjaan berdampak pada pelaksanaan yang representatif, perubahan hierarki mempengaruhi pemenuhan pekerjaan (Harahap, 2020). Pemenuhan pekerjaan jelas mempengaruhi pelaksanaan perwakilan dan terdapat pengaruh positif antara budaya hierarki terhadap pemenuhan pekerjaan (Panjaitan, 2022). Perusahaan membutuhkan job satisfaction yang mampu meningkatkan employee performance.…”
Section: Employee Engagement Pada Job Satisfactionunclassified
“…Full involvement and participation in work will improve employee performance and participate actively in completing their duties. Vice versa, if workers are less involved in decision making, it will create a tendency which is characterized by decreased motivation to work and try to avoid work (Panjaitan, 2018).…”
Section: Sources Of Stress For MI Al-qomar Nganjuk Teachers During Th...mentioning
confidence: 99%